2016
DOI: 10.1038/hr.2016.30
|View full text |Cite|
|
Sign up to set email alerts
|

Increased neutrophil to lymphocyte ratio in persons suffering from hypertension with hyperhomocysteinemia

Abstract: The neutrophil to lymphocyte ratio (NLR) is increased in various cardiovascular diseases. The objective of this study is to determine whether the NLR is increased in persons suffering from hypertension with hyperhomocysteinemia (HTH). We retrospectively analyzed the results of a large cohort of individuals undergoing health examinations with respect to NLR values, homocysteine (HCY) concentration, total cholesterol, triglyceride (TG) concentration, glucose concentration, creatinine (Cr) concentration, smoking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In the hypertension patients, the NLR value increased and positively correlated with hyperhomocysteinemia [19]. In the pathogenesis of aneurysm of the ascending aorta in hypertensive patients, NLR as a marker of inflammation may play an important role [20].…”
Section: Discussionmentioning
confidence: 99%
“…In the hypertension patients, the NLR value increased and positively correlated with hyperhomocysteinemia [19]. In the pathogenesis of aneurysm of the ascending aorta in hypertensive patients, NLR as a marker of inflammation may play an important role [20].…”
Section: Discussionmentioning
confidence: 99%
“…A study on resistance hypertension showed that NLR level was increased in hypertension patients and the resistance hypertension group had a significantly higher NLR than the control hypertension group ( P  = 0.03) [23]. Hypertensive patients with high homocysteine(HCY) had increased NLR and it positively correlated with HCY but not with blood pressure [24]. Also, there was a statistically significant positive correlation between the ascending aortic diameter and NLR ( r  = 0.524, P  < 0.001), which indicated that it plays a role in the pathogenesis of aneurysm of the ascending aorta in hypertensive patients [25].…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Hematological testing was performed on the Advia 120 (Bayer Diagnostics, Newbury, UK), an automated hematology analyzer. Biochemical parameters (glucose, total cholesterol, triglycerides, high-density lipoprotein cholesterol, uric acid and creatinine) were evaluated by enzymatic techniques in an AU640 Olympus Auto Analyzer (Olympus, Tokyo, Japan).…”
Section: Laboratory Proceduresmentioning
confidence: 99%